Investigation of schmallenberg virus seroprevalence in honamlı goats from Burdur region - Varol, Kemal (Afyon Kocatepe Üniversitesi)
Schmallenberg virus (SBV) was first reported in cattle, in north-western Germany and east of the Netherlands in November 2011. SBV causes serious economic losses in domesticated ruminant animals. SBV is also seen in Turkey and there are few seroprevalence studies in cattle, sheep and goats. For this purpose, in this study, the prevalence of SBV was investigated in Honamlı goats in Burdur region. The study was carried out in 12 different herds that were breeding Honamlı goats in Burdur province. The animal material consisted of 186 Honamlı goats with 93 aborted and 93 normal healthy births which were aged between 2-5 years. In the findings; SBV specific antibodies were detected in only two (1.1 %) serum samples from the animals included in the study. In two goats (1.1 %), the test result was suspectable for antibody positivity. Consequently, it was determined that SBV infection has a low seroprevalence rate in Honamlı goats in Burdur province.

Schmallenberg virüsü (SBV) ilk olarak Kasım 2011'de kuzeybatı Almanya'da ve Hollanda'nın doğusunda sığırlarda rapor edilmiştir. SBV evcil geviş getiren hayvanlarda ciddi ekonomik kayıplara yol açmaktadır. SBV ülkemizde de görülmektedir ve sığırlarda ve koyunlarda ve keçilerde az sayıda seroprevalans çalışmaları bulunmaktadır. Fakat Honamlı ırkı keçilerde yapılan seroprevalas çalışması yoktur. Bu amaçla bu çalışmada Burdur yöresinde Honamlı ırkı keçilerde SBV prevalansı araştırılmıştır. Bu çalışma Burdur ilinde Honamlı keçisi yetiştiren 12 farklı sürüde yürütülmüştür. Hayvan materyalini 2-5 yaşları arasında değişen 93 abortlu ve 93 normal sağlıklı doğum yapan 186 Honamlı keçi oluşturmuştur. Bulgularda; Çalışmaya dahil edilen hayvandan kan serumlarının yalnızca ikisinde (% 1.1) Schmallenberg virus spesifik antikor varlığı saptandı. iki keçide ise (% 1.1) test sonucu şüpheli antikor pozitiflik belirlenmiştir. Sonuç olarak; Burdur ilinde Honamlı ırkı keçilerde SBV enfeksiyonunun düşük seroprevalans oranına sahip olduğu belirlenmiştir.
Burdur Yöresi honamlı ırkı keçilerde schmallenberg virüs seroprevalansının araştırılması
Keywords: ELISA; Goat; Honamlı Goat; Schmallenberg Virus; Seroprevalence; Honamlı Keçisi; Keçi; Schmallenberg Virus; Seroprevalans